2010
DOI: 10.1080/09515089.2010.490941
|View full text |Cite
|
Sign up to set email alerts
|

Philosophical temperament

Abstract: Many philosophers have worried about what philosophy is. Often they have looked for answers by considering what it is that philosophers do. Given the diversity of topics and methods found in philosophy, however, we propose a different approach. In this article we consider the philosophical temperament, asking an alternative question: What are philosophers like? Our answer is that one important aspect of the philosophical temperament is that philosophers are especially reflective: They are less likely than thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
55
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(62 citation statements)
references
References 18 publications
2
55
0
Order By: Relevance
“…On the other hand, some evidence suggests that philosophers in particular might be unusually skilled at reasoning. Livengood, Sytsma, Feltz, Scheines, and Machery (2010) found that philosophers exhibited superior performance on the Cognitive Reflection Test, a series of simple math problems prone to incorrect intuitive responding (Frederick, 2005), and Kuhn (1991) found that philosophy graduate students were substantially more skilled in evaluating arguments and evidence than were comparison groups, including schoolteachers (though Cheng et al (1986) find no improvement in Wason Selection Task reasoning for undergraduate students after a 40-h lecture course in formal logic).…”
Section: Prior Researchmentioning
confidence: 96%
“…On the other hand, some evidence suggests that philosophers in particular might be unusually skilled at reasoning. Livengood, Sytsma, Feltz, Scheines, and Machery (2010) found that philosophers exhibited superior performance on the Cognitive Reflection Test, a series of simple math problems prone to incorrect intuitive responding (Frederick, 2005), and Kuhn (1991) found that philosophy graduate students were substantially more skilled in evaluating arguments and evidence than were comparison groups, including schoolteachers (though Cheng et al (1986) find no improvement in Wason Selection Task reasoning for undergraduate students after a 40-h lecture course in formal logic).…”
Section: Prior Researchmentioning
confidence: 96%
“…Here, we embrace a thin characterization of reflection, as was done in previous empirical work on the reflection defense: A judgment is thinly reflective just in case it results from a deliberation process involving attention, focus, cognitive effort, and so on-the type of domain-general psychological resources that careful and attentive thinking requires-and unreflective otherwise. We examined the possible effect of reflection by looking at people's disposition to engage in reflection, using the CRT as our measure (as was done in Livengood, Sytsma, Feltz, Scheines, & Machery, 2010).…”
Section: Reflectionmentioning
confidence: 99%
“…There is an open debate over the extent to which philosophy provides certain skills (e.g., critical thinking skills) or instead whether students who possess these skills tend to become philosophy majors (Livengood et al 2010). However, it would remain true even on the second view that a philosophy degree is a reliable indicator of these skills, and that women who possess these skills but do not have a philosophy credential may be less likely to be perceived as having the skills.…”
Section: Section 2: Why Study Underrepresentation Of Women In Philosomentioning
confidence: 99%
“…These cognitive and socially critical skills are prized across a wide range of careers in business, technology, law, journalism, politics, medicine, and other non-academic jobs. To the extent that, in disproportionate numbers, undergraduate women choose not to take philosophy courses beyond the introductory level, they may not be getting the same value for their educational dollar as male students and risk missing out on career opportunities and benefits that these skills provide.There is an open debate over the extent to which philosophy provides certain skills (e.g., critical thinking skills) or instead whether students who possess these skills tend to become philosophy majors (Livengood et al 2010). However, it would remain true even on the second view that a philosophy degree is a reliable indicator of these skills, and that women who possess these skills but do not have a philosophy credential may be less likely to be perceived as having the skills.…”
mentioning
confidence: 99%